(untitled) (Archive of Conferences, 2021)
The word is the most important part of any language. There is a fairly large amount of theoretical information about the "word": definition, occurrence, analogues of it in other languages, etc. But despite this, most people experience problems when learning a particular language. Why is language easy for someone, but not for someone? In this paper I have tried to answer this question and give examples of how to study lexical units of Russian or any other language